1999
DOI: 10.1002/(sici)1099-1166(199912)14:12<1019::aid-gps61>3.3.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Decreased awareness of cognitive deficits in patients with mild dementia of the Alzheimer type

Abstract: The nature of unawareness of cognitive deficits appeared to be more dimensional than categorical. In patients with mild dementia, decreased awareness appeared to be more related to affective disturbances, especially to emotional deficit or apathy, than to cognitive deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
2
37

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(144 citation statements)
references
References 33 publications
7
98
2
37
Order By: Relevance
“…These fi ndings concur with previous studies, which have consistently found correlations between clinical ratings and questionnaire discrepancies (Derouesné et al, 1999 ;Howorth and Saper, 2003 ;Ott et al, 1996 ;Vogel et al, 2004), but not between performance discrepancies and questionnaire discrepancies or clinical ratings (Correa et al, 1996 ;Duke et al, 2002 ;Green et al, 1993 ;Hannesdottir and Morris, 2007 ;Howorth and Saper, 2003 ). This lack of overlap may exist because different measures tap into different aspects of self-awareness which are not uniformly impaired.…”
Section: Discussionmentioning
confidence: 99%
“…These fi ndings concur with previous studies, which have consistently found correlations between clinical ratings and questionnaire discrepancies (Derouesné et al, 1999 ;Howorth and Saper, 2003 ;Ott et al, 1996 ;Vogel et al, 2004), but not between performance discrepancies and questionnaire discrepancies or clinical ratings (Correa et al, 1996 ;Duke et al, 2002 ;Green et al, 1993 ;Hannesdottir and Morris, 2007 ;Howorth and Saper, 2003 ). This lack of overlap may exist because different measures tap into different aspects of self-awareness which are not uniformly impaired.…”
Section: Discussionmentioning
confidence: 99%
“…Marcel et al (2004) found that responses to questions framed in the third person reflected greater awareness of hemiplegia than questions framed in the first person. In relation to AD, Derouesné et al (1999) and Kaszniak and Christenson (1996) have noted that results from different methods of assessing unawareness are not closely correlated, and that the presence and degree of awareness deficits elicited varies according to the assessment methods used. This might go some way, therefore, to explaining some of the anomalies in the literature.…”
Section: Integrating Different Levels Of Explanationmentioning
confidence: 99%
“…Other approaches have employed combinations of both clinician-rated assessments and discrepancy measures in an attempt to provide a more global and comprehensive picture of awareness or insight (Correa et al, 1996;Derouesné et al, 1999;Howorth & Saper, 2003;Ott et al, 1996). In addition, some studies have included novel ways of assessing awareness.…”
Section: Composite and Other Methodsmentioning
confidence: 99%
“…Examining the different approaches taken to assess awareness clinically, it is evident from the above that the phenomena of awareness determined by the various measures are likely to be different. There is also some empirical confirmation of this in that studies using different measures of awareness concomitantly have obtained different clinical outcomes in relation to the particular measure of awareness used (Derouesné et al, 1999;Duke et al, 2002;Green et al, 1993;Howorth & Saper, 2003;Sanz et al, 1998;Sevush, 1999). If the clinical phenomena of awareness are different in relation to the different approaches taken to evaluate awareness, questions then follow concerning the nature of such differences and the implications they carry for understanding insight, in terms of its structure, its role in disease states and in terms of its practical application in relation to communication with and management of patients with various disabilities.…”
Section: The Phenomenon Of Awareness As Determined By Empirical Measuresmentioning
confidence: 99%
See 1 more Smart Citation